The stabilization interval system of a tethered descent underwater vehicle; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Gaivoronsky (Gayvoronsky) S. A. Sergey Anatolievich; Ezangina T. A. Tatiana Aleksandrovna; Khozhaev I. V. Ivan Valerievich; Efimov S. V. Semyon Viktorovich (Integrated Computer Control Systems in Mechanical Engineering, 2016)
Title screen